Federal Lands: The quilombola community Bom Jardim da Prata and territorial disputes in the Middle Valley of São Francisco/MG: Federal Lands: The quilombola community Bom Jardim da Prata and territorial disputes in the Middle Valley of São Francisco/MG - Sérgio Marques, Amaro; Borsagli, Alessandro; Melo Bernardes, Brenda (Revista Desenvolvimento Social, 2023)
Since the process of colonization of Brazil, the São Francisco River has attracted traditional peoples, who mainly inhabit its banks, due to the facilities associated with river transport, the possibility of using its waters for daily activities and the fertility of the soils located near the watercourse for cultivation. Despite this direct dependence of the traditional communities on the São Francisco River as a source of subsistence, throughout history there have been conflicts between these peoples and other social groups that have also shown interest in enjoying the benefits of the river and the fertility of its lands, through the predatory exploitation of natural resources for economic purposes. However, these lands legally belong to the Federal Government, which makes the existing territorial conflicts even more problematic. Thus, the objective of this article is to understand the existing problems linked to the process of occupation of federal lands by different social groups and the existing economic interests. The analysis presented presents the Middle Valley of São Francisco region as a study setting, with emphasis on the territorial conflicts linked to the quilombola community of Bom Jardim da Prata, located in the rural region of the municipality of São Francisco, with emphasis on the territorial conflicts linked to the quilombola community of Bom Jardim da Prata, located in the rural region of the municipality of São Francisco.